An investigation into the toxicity of tissue extracts from two distinct marine Polychaeta. (June 2022) - D'Ambrosio, Mariaelena; Ramos, Íris; Martins, Carla; Costa, Pedro M.
Abstract: The present study investigated the potential toxicity of venomous secretions of two polychaetes, Hediste diversicolor and Glycera alba (Annelida: Phyllodocida). Toxic activity of putative toxins, measured on mussel gills through the Comet assay, revealed higher effects caused by extracts from H. diversicolor skin and G. alba specialised, jawed proboscis, when compared to control. The results suggest that H . diversicolor secretes toxins via skin for protection against predators, contrarily to G. alba, who secretes toxins for predation. Graphical abstract: Image 1 Highlights: Hediste diversicolor and Glycera alba secrete bioactive compounds. The Comet assay on mussel gills indicates the toxic nature of secretions. Higher toxicity of G. alba proboscis secretions suggests specialisation for preying. H. diversicolor skin secretions can be less specialised and used defence.